Agnieszka Matyjaszczyk Grenda Universidad Complutense de Madrid – ITEM - Matyjaszczyk , Agnieszka (Pygmalion. Revista de teatro general y comparado, 2025)
Agnieszka Matyjaszczyk Grenda Universidad Complutense de Madrid – ITEM